The role of avian scavengers in the breakdown of carcasses in pastoral landscapes. (2nd January 2017) - Peisley, Rebecca K.; Saunders, Manu E.; Robinson, Wayne A.; Luck, Gary W.
ABSTRACT: Scavenging birds can provide ecosystem services to pastoralists by contributing to the breakdown of animal carcasses that can harbour and spread disease. However, these benefits have yet to be quantified in Australia. We monitored rabbit carcasses using motion-sensor cameras to identify beneficial avian scavengers across four landscape types (forest, riparian, fields with large isolated trees, and open fields) on a pastoral property in north-central Victoria. We quantified the ecosystem service of carcass breakdown by measuring the per cent weight loss of carcasses exposed to scavenging birds compared to carcasses excluded from birds. Seven of the twenty-four bird-accessible carcasses were attacked by raptors in 2014, and three in 2015. When a raptor attacked a carcass, there was a significantly higher median per cent weight loss of the carcass (16.67%, interquartile range (IQR) = 8.33–100.0) compared with sites where no bird attacks occurred (6.65%, IQR = 3.03–12.06). Our results indicate that raptors are major contributors to carcass breakdown in grazing landscapes and may potentially contribute to reducing the spread of diseases such as blowfly strike and leptospirosis. Maintaining key habitat features for these species (e.g. large isolated trees) is essential for raptor conservation and maximising the ecosystem services they provide.